Pengelolaan Pembelajaran IPS Kelas V di SDN 3 Tegalrejo Kecamatan Wirosari Kabupaten Grobogan - SUGIRI, SUGIRI, Prof. Dr. Bambang Sumardjoko, Dr. Sumardi, M.Si (2016)
This study aimed to describe: (1) the way teachers grade V SDN 3 Tegalrejo District of Wirosari Grobogan in planning the management of learning social studies, (2) the way teachers grade V SDN 3 Tegalrejo District of Wirosari Grobogan in carrying out social studies learning, and (3 ) means the fifth grade teacher at SDN 3 Tegalrejo Wirosari District of Grobogan in assessing learning outcomes IPS. This research is qualitative. The collection of data obtained by in-dept interviews, observation and analysis of the selected dokumentasi.Informan V class is the teacher, principal, and siswa. Keabsahan source data using triangulation techniques and triangulation techniques. Results from the study showed that: (1) how the fifth grade teacher in planning learning social studies program is to prepare lesson materials for each meeting in accordance with the standards of competence and basic competences. Plans were made teachers in the form of Learning Implementation Plan. In addition to materials, the lesson plan also contains learning objectives, learning methods, and assessment of learning outcomes. (2) The learning process begins with IPS Class V: (a) the initial activity of learning to say hello, check the attendance of the students, deliver learning objectives, and do apperception; (B) the fifth grade teachers manage the learning process by way of delivering materials to students using lectures, discussion, group discussion, demonstration, and deployment. The teacher divides the students into several groups, to guide students in discussions, and provide feedback on students' work; and (c) terminate the teacher learning material concluded, give evaluation and moral message to the students. (3) the results of social studies conducted by engineering tests, both written tests and oral tests. Instruments used by teachers in the form of multiple choice questions and short answers. Keywords: learning, management, IPS